The Role of Information and Communication Technology (ICT) and Tourism on Economic Growth in Indonesia - Audina, Resda Aninditya; Kartiasih, Fitri; Yuliana, Rita (Faculty of Economics, Universitas Sriwijaya, 2024)
This study aims toanalyze the influence of ICT and the tourism sector on economic growth in Indonesia from 2015 to 2021 using panel data regression analysis on a total of 238data with the Feasible Generalized Least Square-Seemingly Unrelated Regression (FGLS-SUR) estimation method. The results of the study show that the proportion of individuals who use the internet, the number of fixed broadband subscribers, the room occupancy rate of star hotels, foreign investment, labour, and government spending have a positive and significant effect on economic growth in Indonesia. In this regard, it is hoped that each province will have equal access to the internet and further enhance hotel services, especially for star-rated hotels.The positive impact of this research in Indonesia is that it can help enhance the Gross Regional Domestic Product (GRDP) in each province, thereby influencing overall economic growththrough the fields of ICT and tourism.